Global Immunization Vision and Strategy (IVS) : a mid-term analysis of progress in 50 countries (2013)
Reviews the performance of 50 countries which have developed comprehensive Multi-Year Plans (cMYPs) since the inception of the Global Immunization Vision and Strategy (GIVS) and cMYP guidelines in 2005.
Keywords: IMMUNIZATION